2014
DOI: 10.3201/eid2007.131118
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathogenic Fowlpox Virus in Cutaneously Infected Chickens, China

Abstract: We investigated an acute outbreak of the cutaneous form of fowlpox among chickens in China in November 2009. Using pathologic and virologic methods, we identified a novel type of fowlpox virus that carried an integrated genomic sequence of reticuloendotheliosis virus. This highly pathogenic virus could lead to severe ecologic effects and economic losses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 13 publications
(9 reference statements)
2
32
0
Order By: Relevance
“…The disease has reemerged as a new threat to poultry farmers and a number of outbreaks have been reported in non-vaccinated as well as vaccinated flocks [7,9,10]. Several workers had characterized the field strains of FWPV and found incorporation of reticuloendotheliosis (REV) provirus in their genome [11][12][13][14][15][16]. The REV is transmitted through integration of REV provirus in FWPV genome and has been recorded prior to 1949 [17].…”
Section: Introductionmentioning
confidence: 99%
“…The disease has reemerged as a new threat to poultry farmers and a number of outbreaks have been reported in non-vaccinated as well as vaccinated flocks [7,9,10]. Several workers had characterized the field strains of FWPV and found incorporation of reticuloendotheliosis (REV) provirus in their genome [11][12][13][14][15][16]. The REV is transmitted through integration of REV provirus in FWPV genome and has been recorded prior to 1949 [17].…”
Section: Introductionmentioning
confidence: 99%
“…The diphtheritic variety of fowlpox is characterized by the presence of elevated yellowish spots on the mucous membranes of the mouth, esophagus, trachea and lungs, which can result in dyspnoea or swallowing. In both cases, birds may be weak and exhausted (Zhao et al, 2014). We have also found that the clinical signs of the disease in chickens were characterized by lethargy, mild to severe dyspnoea, conjunctival redness, excessive tearing, palpebral and paranasal sinus edema.…”
Section: Discussionmentioning
confidence: 85%
“…It has been reported that Avipoxvirus is caused by symptoms such as the appearance of pustules in the skin of birds, as well as signs of disease similar to diphtheria, which may include characteristic necrotic lesions covering the oral cavity and upper respiratory tract (Zhao et al, 2014), which may be due to the fact that, like other avian viruses, the fowlpox virus can be transmitted through vectors mechanically, for example, through mosquitoes. Other authors note that in this disease the virus affects the mucous membranes of the pharynx, larynx and, more rarely, the epithelium of the lower respiratory tract (Bande et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It's used to differentiate FPV from other APVs because it's highly conserved. FPV140 is highly antigenic and immunodominent [1][2][3][4]6,[8][9][10][11][12][13][14][15]17,18].…”
Section: Fpv Related To Genus Avipox (Apvs) Apvs Belong To Subfamilymentioning
confidence: 99%
“…This form has high currency but it's mild. The severe form is the wet type known as diphtheritic infection which infects mucus membrane of respiratory and gastrointestinal tract especially (larynx, pharynx and mouth) is featured by necrotic lesions, this type cause death more than dry type due to suffocation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%